2006
DOI: 10.1038/nature04330
|View full text |Cite
|
Sign up to set email alerts
|

Bile acids induce energy expenditure by promoting intracellular thyroid hormone activation

Abstract: While bile acids (BAs) have long been known to be essential in dietary lipid absorption and cholesterol catabolism, in recent years an important role for BAs as signalling molecules has emerged. BAs activate mitogen-activated protein kinase pathways, are ligands for the G-protein-coupled receptor (GPCR) TGR5 and activate nuclear hormone receptors such as farnesoid X receptor alpha (FXR-alpha; NR1H4). FXR-alpha regulates the enterohepatic recycling and biosynthesis of BAs by controlling the expression of genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

63
1,711
11
24

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,904 publications
(1,809 citation statements)
references
References 22 publications
63
1,711
11
24
Order By: Relevance
“…As bile acids were shown to increase the metabolic rate in mice, it can be speculated that FXR (NR1H4), which is activated by bile acids, may influence body weight through an effect on energy expenditure. 46 This study showed a very high BMI and waist in the four women with the SMARCA2 intron 9 AA genotype. All of them were overweight and three were obese.…”
Section: Discussionmentioning
confidence: 53%
“…As bile acids were shown to increase the metabolic rate in mice, it can be speculated that FXR (NR1H4), which is activated by bile acids, may influence body weight through an effect on energy expenditure. 46 This study showed a very high BMI and waist in the four women with the SMARCA2 intron 9 AA genotype. All of them were overweight and three were obese.…”
Section: Discussionmentioning
confidence: 53%
“…Since FXR requires bile salt binding to act to control expression target genes, Bsep may, by controlling bile salt concentration in systemic circulation, become an important control element in body energy and lipid homeostasis. And finally, bile salts have recently been shown to control energy expenditure by controlling intracellular thyroid hormone action by binding to the G protein-coupled receptor TGR5 [43,101].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, mice fed bile acids in conjunction with a high fat diet (HFD) are resistant to diet-induced obesity, but D2KO mice are not. This appears to be dependent upon increased D2 expression induced by bile acids in BAT during a high fat diet, although D2 in other tissues may have a role in this as well (49). A potential metabolic role for D2 has also been suggested in human studies in patients receiving replacement doses of T4; in these subjects basal metabolic rate correlates directly with free T4 and inversely with serum TSH but not with free T3 (50).…”
Section: Deiodinases and Metabolic Controlmentioning
confidence: 97%